Bone marrow mesenchymal stem cell-derived exosomes enhance osteoclastogenesis during alveolar bone deterioration in rats. Issue 34 (13th April 2017) - Xu, Shuyu; Wang, Zuolin
Abstract : BMMSC-derived exosomes from rats with bone deterioration increased the osteoclastogenesis of the Raw264.7 cells, which suggests that BMMSC-derived exosomes could accelerate osteoclastogenesis in alveolar bone deterioration. Abstract : Healthy and functional alveolar bones to support implants or dentures are fundamental for dental restoration. Osteoporosis, which leads to alveolar bone resorption, is a common disease, especially in elderly patients with tooth loss. Enhanced osteoclastogenesis is the main pathogenesis of bone resorption, which is related to the paracrine regulation of BMMSCs (bone marrow mesenchymal stem cells). Furthermore, exosomes have been substantiated to be involved in the paracrine functions of BMMSCs. However, the underlying mechanisms of the regulation of exosomes in osteoclastogenesis remain unclear. The aim of this study is to investigate the role of BMMSC-derived exosomes in regulating osteoclastogenic differentiation of the osteoclast precursor cell line Raw264.7 to illustrate the role of exosomes in alveolar bone resorption. To establish the rat model of alveolar bone osteoporosis, thirty ten-week-old female SD rats were subjected to ovariectomy (OVX) or sham-operation. One month later, the right maxillary molars were extracted. Three months after tooth extraction (TE), the maxillae were collected. The BMMSCs of the alveolar bones from the SHAM + TE, OVX and OVX + TE groups were retrieved and cultured for the isolation of exosomes. The Raw264.7 cells were co-cultured with BMMSC-derived exosomes to investigate their osteoclastogenic differentiation. In vivo, OVX and tooth loss exerted a synergistic effect on the upregulation of osteoclastogenesis, which led to bone resorption. In vitro, the BMMSC-derived exosomes from the rats with bone deterioration (SHAM + TE, OVX and OVX + TE) increased the osteoclastogenesis of the Raw264.7 cells. These results suggest that BMMSC-derived exosomes could accelerate osteoclastogenesis in alveolar bone deterioration.